Prevention and control of tuberculosis in workplaces: how knowledgeable are the workers in Bangladesh? - Islam, Qazi Shafayetul; Islam, Md Akramul; Islam, Shayla; Ahmed, Syed Masud (BMC Public Health, 2016)
Includes bibliographical references (page 9-10).